Sustainable antimicrobial nanocomposite coatings with enhanced durability for outdoor construction materials - Gámez Espinosa, Erasmo Junior (2025)
The biodeterioration of construction materials compromises their durability and increases maintenance costs. This study evaluates the long-term antimicrobial performance and structural stability of water-based nanocomposite coatings incorporating functionalized nanomaterials obtained by green synthesis. These nanocomposite coatings, consisting of a polymeric matrix reinforced with tannin-derived silver nanoparticles (AgNPs), were applied to ceramic materials and exposed to natural weathering for 2.5 years. Characterization results showed adequate hiding power, drying time and wet-scrub resistance exceeding 4000 cycles, with the nanostructured formulation (PQ) exhibiting superior dispersion (30–40 μm) compared to the control paint (80–90 μm). The results show that PQ markedly reduced microbial growth (rating 1 vs. 4 for the control, ASTM D5590), while preserving chemical stability and integrity over time. Importantly, this work provides the first evidence of the long-term outdoor performance of exterior paints functionalized with AgNPs synthesized from Schinopsis balansae tannin. These findings highlight the potential of tannin-derived nanomaterials as sustainable additives in advanced protective nanocomposite coatings, contributing to enhanced durability, structural integrity and reduced maintenance of construction materials in outdoor environments.